국회기록관리위원회 안건 분석을 통한 국회기록관리 정책 연구 - 성면섭(Myeon-seob Seong); 김장환(Janghwan Kim) (Journal of Records Management & Archives Society of Korea, 2021)
The National Assembly's archives management policy is deliberated by the National Assembly Archives Committee before it is implemented. This study tried to identify the agenda of the committee, which acts as a basis for establishing and implementing the archives management policies, and confirm whether various policies dealt with all fields of archives management. Accordingly, the committee meeting data, minutes, and related laws were checked. Focusing on the agenda, the continuity and diversity of the overall policy, whether there is a bias toward specific policy issues, and the main discussion subject of the committee about the archives management policy were analyzed. As a result of confirming the entire agenda, the agenda related to the archives management policy has been made up of reporting agendas, and as a result, it has emerged that various and in-depth discussions related to policies have not been conducted well. However, it was confirmed that the overall archives management policy was carried out with continuity for many years without focusing on a specific sector. 국회의 기록관리 정책은 실행되기에 앞서 국회기록관리위원회의 심의를 거친다. 이 연구는 기록관리 정책 수립 및 추진의 기반으로 작용하는 위원회의 안건을 파악해, 국회의 각종 기록관리 정책이 전 분야를 다루었는지 확인하고자 했다. 이에 위원회 회의자료 및 회의록, 관련 법규를 확인하고, 안건을 중심으로 전체 정책의 연속성 및 다양성, 특정 정책사항에 대한 편중성 여부, 정책사항에 대한 위원회의 주요 논의사항 등을 중점적으로 분석하였다. 전체 안건 확인 결과, 지금까지 위원회에서 기록관리 정책 관련 안건은 보고안건으로 이루어졌고, 이로 인해 정책 관련 다양하고 깊은 논의가 잘 이루어지지 않았다. 그렇지만 전반적인 기록관리 정책이 특정 부문에 치중되지 않고 다년간 연속성을 가지고 추진되었음을 확인하였다.